Gesture changes thought by grounding it in action - Beilock, S.L. (2010)
When people talk, they gesture. We show that gesture introduces action information into speakers’ mental representations, which, in turn, impact subsequent performance. In Exp.-1, participants (a) solved the Tower-of-Hanoi task (TOH1); (b) explained (with gesture) how they solved it; (c) solved it again (TOH2). For all participants, the smallest disk in TOH1 was lightest and could be lifted with one-hand. For some participants (No-Switch Group), disks in TOH2 were identical to TOH1. For others (Switch Group), disk weights in TOH2 were reversed (smallest disk=heaviest and could not be lifted one-handed). The more the Switch group’s gestures depicted moving the smallest-disk one-handed, the worse they performed on TOH2. This was not true for the No-Switch Group, nor for the Switch Group in Exp.-2 who skipped the explanation step and did not gesture. Gesturing grounds people’s mental representations in action. When these gestures are no longer compatible with the action constraints of the task, problem solving suffers.